Long-term follow-up observations confirm the stability of hemoglobin F levels in patients with hemoglobinopathies receiving metformin therapy - Hassan, Moataz Mohamed; Hassan, Myaysa Mohamed; Abdullatif, Hussein; Khan, Hammad; El-Ghamry, Islam; Qureshi , Rizwan Nabi; Panjwani , Vinodh; Al-Qarni, Zahra; Abdulhakem, Esraa; Wali, Yasser; Boulassel, Mohamed-Rachid (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: There is limited real-world evidence on how metformin use may affect fetal hemoglobin (HbF) levels in patients with hemoglobinopathies. This study describes long-term changes in HbF levels in patients with sickle cell anemia (SCA) and thalassemia major who continuously received metformin at a standard dose for type 2 diabetes.Methods: Adult patients taking metformin for at least 6 months and had at least three different time points of HbF assessments at three months apart were included. Pharmacy refill records were used to evaluate adherence to metformin. Data were collected before metformin therapy, and during routine follow up visits. Comparisons were performed using the Wilcoxon matched pairs test.Results: Over a period of ten years, five patients with SCA (71%) and two (29%) with thalassemia major were enrolled. Metformin was administered orally at doses ranging from 1000 to 2000 mg per day, either alone or concurrently with hydroxyurea. Among the participants, four patients (57%) underwent allogeneic bone marrow transplantation after 12 to 60 months of initiation of metformin therapy. When compared to baseline levels, HbF levels did not exhibit a significant change following one to eight years of metformin therapy alone or in combination with hydroxyurea  (P=0.58).Conclusions: Collectively, our findings indicate that the clinical utilization of metformin at standard doses, either alone or added to hydroxyurea does not have any additional effect on HbF levels among patients with hemoglobinopathies even after several years of therapy.